Austria : Recent Economic Developments and Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in Austria during 1995-96. A review of developments and short-term prospects for the domestic economy, the public finances, monetary and exchange rate policy, and the balance of payments is presented. Several estimates of potential output and the output gap in Austria are discussed, together with two macroeconomic scenarios that the IMF staff has developed. The paper provides an analysis of the Austrian federal structure. The distribution of government responsibilities, the revenue-sharing mechanism, and transfers among different levels of government are also discussed.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet